Heat-sensitive material as well as preparation method and application thereof

Thermal-sensitive materials prepared by combining biomass matrix with thermally sensitive monomers have solved the problems of low recovery efficiency of rare earth ions and limited environmental protection of desorption methods in the prior art, and the efficient adsorption and sustainable desorption of rare earth ions are achieved, which has environmental protection and economic advantages.

CN119638895APending Publication Date: 2025-03-18INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411825853.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art cannot effectively recover low-concentration rare earth ions, resulting in rare earth erosion and water pollution. The adsorption method depends on acid leaching method and environmental protection is limited.

Method used

A thermally sensitive material is developed to prepare a rare earth ion adsorption material with good adsorption and selectivity by combining a biomass matrix with a thermally sensitive monomer, and to achieve reversible desorption of rare earth ions by rinsing cold water.

Benefits of technology

The efficient adsorption and sustainable desorption process of rare earth ions is achieved, which avoids dependence on acid elution and sorption, reduces environmental pollution and production costs, and has good economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638895A_ABST
    Figure CN119638895A_ABST
Patent Text Reader

Abstract

The invention relates to a heat-sensitive material as well as a preparation method and application thereof. The preparation raw materials of the heat-sensitive material comprise a biomass matrix, a heat-sensitive monomer and a cross-linking agent. By matching the biomass matrix and the thermosensitive monomer, the biomass matrix and the thermosensitive monomer play a synergistic effect, so that the rare earth ion adsorbent has good adsorbability and selectivity on rare earth ions, and separation and recovery of the rare earth ions are further facilitated; meanwhile, when the heat-sensitive material is used as an adsorbent, after rare earth ions are adsorbed, the rare earth ions can be desorbed through cold water flushing, repeated recycling of the adsorbent is achieved, the whole operation process is simple, green and safe, use of organic solvents is avoided, secondary pollution to the environment is reduced, production cost is reduced, and the heat-sensitive material is suitable for industrial production. And good economic benefits are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adsorption materials, and in particular to a thermosensitive material and a preparation method and application thereof. Background Art

[0002] Rare earth elements have become important mineral resources due to their excellent magnetic, optical and electrical properties, and are known as "a treasure trove of new materials" and "vitamins of industry". However, the current ammonium bicarbonate precipitation transformation process cannot effectively recover low-concentration rare earth ions in the in-situ leaching solution, causing serious rare earth loss and water pollution problems. Therefore, it is urgent to develop a method for separating and recovering rare earth ions from low-concentration wastewater.

[0003] At present, the extraction of rare earth metals in industrial production generally adopts liquid-liquid extraction technology. A large amount of organic solvents are used in the extraction process, which not only produces by-products but also produces a large amount of organic waste liquid, thus causing secondary pollution. In contrast, the adsorption method is considered to be a method with good application prospects for the recovery and separation of low-concentration metal ions due to its excellent separation effect, simple operation process, no need for additional auxiliary conditions, low energy consumption, and the ability to selectively adsorb and separate low-concentration metal ions in wastewater by selecting different adsorbents and classifying and enriching them.

[0004] Ion-imprinted polymers have attracted attention due to their ability to recognize certain ions at specific sites and their tolerance to acids and bases. Ion-imprinted technology (IIT) is an effective means to achieve selective adsorption of target ions. However, the common method for ion desorption is acid leaching, which removes ions by immersion in inorganic acids. This method is not conducive to environmental protection and seriously limits the further promotion of adsorption methods and IIT.

[0005] CN103521197A discloses a method for preparing a light rare earth ion imprinted adsorbent for treating rare earth wastewater. The obtained light rare earth ion imprinted adsorbent can realize the adsorption and recovery of rare earth ions. However, during its preparation, it is necessary to soak in a sulfuric acid solution (3 mol / L) for 24 hours to remove the rare earth imprinted ions. CN115141305A discloses a functional polymer and a preparation method, and a method for preparing an ion imprinted polymer using the same. During the preparation of the ion imprinted polymer, it is necessary to repeatedly wash with 0.1 mol / L hydrochloric acid to remove the template ions.

[0006] Therefore, it is of great significance to design and develop a more environmentally friendly technology so that the obtained adsorbent material not only has a good adsorption effect on rare earth ions but also has a sustainable desorption process. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a thermosensitive material and a preparation method and application thereof. The thermosensitive material can be used for rare earth ion adsorption and has the characteristics of water-washing desorption of rare earth ions. The preparation process is simple, the selectivity and recyclability are excellent, the dependence of desorption on inorganic acid is solved, and the green and efficient separation and recovery of rare earth ions is realized.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a thermosensitive material, wherein raw materials for preparing the thermosensitive material include a biomass matrix, a thermosensitive monomer and a cross-linking agent.

[0010] The thermosensitive material provided by the present invention has a stable structure. By combining a biomass matrix with a thermosensitive monomer, the two play a synergistic role, thereby having good adsorption and selectivity for rare earth ions, which is beneficial to the separation and recovery of rare earth ions. At the same time, when the thermosensitive material is used as an adsorbent, after adsorbing rare earth ions, it can desorb the rare earth ions by washing with cold water, thereby realizing multiple recycling of the adsorbent. The entire operation process is simple, green and safe, which not only avoids the use of organic solvents and reduces secondary pollution of the environment, but also helps to reduce production costs and has good economic benefits.

[0011] Preferably, the mass ratio of the biomass matrix, the thermosensitive monomer and the cross-linking agent is (1-15):(7-40):(1-3), for example, it can be 1:7:1, 1:20:1, 1:30:1, 1:40:1, 7:7:1, 7:15:1, 7:25:3, 15:7:1, 15:7:3 or 15:40:3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0012] Preferably, the molar ratio of the biomass matrix to the thermosensitive monomer is 1:(3.4-17), for example, it can be 1:3.4, 1:4, 1:5, 1:6, 1:6.4, 1:6.8, 1:8, 1:10, 1:12, 1:13.5, 1:15 or 1:17, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 1:(6.8-13.5).

[0013] In the present invention, the molar ratio of the biomass matrix to the thermosensitive monomer is specifically selected as 1:(3.4-17). When the molar ratio of the two is higher than 1:3.4, the content of the thermosensitive monomer is low, which reduces the active sites of the obtained thermosensitive material, thereby reducing its adsorption performance. When the molar ratio of the two is lower than 1:17, the content of the thermosensitive monomer is too high, resulting in poor thermosensitivity of the obtained thermosensitive material, thereby affecting its stability, and further resulting in poor adsorption performance. Further, when the molar ratio of the two is 1:(6.8-13.5), it has a better adsorption effect. If it is lower or higher than the preferred range, the adsorption amount of the obtained thermosensitive material will be reduced, and at the same time, its selectivity will also deteriorate.

[0014] Preferably, the biomass matrix comprises any one of cellulose nanofibers, chitin nanofibers, carboxymethyl cellulose, bacterial cellulose, chitosan or carboxymethyl chitosan, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of cellulose nanofibers and chitin nanofibers, a combination of carboxymethyl cellulose and bacterial cellulose, a combination of chitosan and carboxymethyl chitosan, or a combination of cellulose nanofibers, chitin nanofibers and chitosan, a combination of bacterial cellulose, chitosan and carboxymethyl chitosan, preferably chitosan and / or carboxymethyl chitosan, further preferably carboxymethyl chitosan.

[0015] In the present invention, the specifically selected biomass matrix is ​​rich in source, non-toxic, has many active sites, and can have good adsorption and selectivity for rare earth ions. Among them, chitosan is a copolymer of N-acetyl-D-glucosamine and D-glucosamine, a unique alkaline polysaccharide, and the most abundant biopolymer on the earth after cellulose. The large amount of amino and hydroxyl groups it contains not only make chitosan have good adsorption properties for metal ions, but also have the possibility of various chemical modifications. Converting chitosan into carboxymethyl chitosan can solve the problem that chitosan is insoluble in neutral water because the amino group remains unprotonated in neutral water, so that carboxymethyl chitosan can be dissolved in water within a wide pH range, greatly expanding its application range. At the same time, in the present invention, carboxymethyl chitosan is used as the biomass matrix, and it is matched with specific thermosensitive monomers, crosslinking agents and other raw materials, so that the obtained thermosensitive material can have better adsorption and selectivity.

[0016] Preferably, the heat-sensitive monomer includes any one of N-isopropyl acrylamide, N-hydroxymethyl acrylamide, N,N-diethyl acrylamide or N-isopropyl methacrylamide, or a combination of at least two thereof.

[0017] Preferably, the cross-linking agent includes any one of N,N-methylenebisacrylamide, glutaraldehyde or acrylamide, or a combination of at least two thereof.

[0018] Preferably, the raw material for preparing the thermosensitive material includes an imprinted ion source.

[0019] Preferably, the imprinted ion source includes any one of light rare earth ions, medium rare earth ions or heavy rare earth ions, or a combination of at least two of them. Typical but non-limiting combinations include a combination of rare earth ions and medium rare earth ions, a combination of rare earth ions and heavy rare earth ions, a combination of medium rare earth ions and heavy rare earth ions, or a combination of rare earth ions, medium rare earth ions and heavy rare earth ions.

[0020] Preferably, the light rare earth ions include lanthanum ions (La 3+ ), cerium ion (Ce 3+ ), praseodymium ion (Pr 3+ ) or neodymium ions (Nd 3+ ) or a combination of at least two of them.

[0021] Preferably, the medium rare earth ions include samarium ions (Sm 3+ ), europium ions (Eu 3+ ), gadolinium ions (Gd 3+ ), terbium ions (Tb 3+ ) or dysprosium ion (Dy 3+ ) or a combination of at least two of them.

[0022] Preferably, the heavy rare earth ions include holmium ions (Ho 3+ ), erbium ions (Er 3+ ), thulium ion (Tm 3+ ), Ytterbium ions (Yb 3+ ), Lutetium ion (Lu 3+ ) or yttrium ion (Y 3+ ) or a combination of at least two of them.

[0023] Preferably, the mass ratio of the imprinted ion source to the biomass matrix is ​​(0.005-0.02):(1-15), for example, it can be 0.005:1, 0.008:1, 0.01:1, 0.015:1, 0.02:1, 0.005:7, 0.01:8 or 0.02:15, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] In the present invention, the addition of a specific content of imprinted ion source enables the thermosensitive material to be prepared by ion imprinting technology. By using the imprinted ion source as a template ion, the obtained thermosensitive material can form a three-dimensional imprinted cavity, thereby effectively improving its adsorption and selectivity for rare earth ions.

[0025] Preferably, the raw materials for preparing the thermosensitive material also include an initiator and a solvent.

[0026] Preferably, the initiator includes any one of ammonium persulfate, azobisisobutyronitrile, benzoyl or potassium persulfate, or a combination of at least two thereof.

[0027] Preferably, the solvent comprises water.

[0028] Preferably, the water includes any one of distilled water, ultrapure water or deionized water, or a combination of at least two of them.

[0029] Preferably, the mass ratio of the biomass matrix and the initiator is (1-15):(30-50), for example, it can be 1:30, 1:40, 5:30, 5:40, 10:40, 10:50, 15:30, 15:40 or 15:50, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] In a second aspect, the present invention provides a method for preparing the thermosensitive material as described in the first aspect, the preparation method comprising the following steps:

[0031] The raw materials including a biomass matrix, a thermosensitive monomer and a cross-linking agent are mixed and reacted to obtain the thermosensitive material.

[0032] The preparation method of the thermosensitive material provided by the present invention is simple and can be synthesized by a "one-pot method" polymerization reaction. The entire preparation process is simple to operate, the raw material source is wide, and the cost is low.

[0033] Preferably, the mixing is performed under stirring.

[0034] Preferably, the stirring is performed in an oil bath.

[0035] Preferably, the reaction is a gradient temperature increase reaction.

[0036] Preferably, the gradient temperature rising reaction comprises the following stages:

[0037] In the first stage, the temperature of the reaction system is 25-32° C. (for example, 25° C., 26° C., 27° C., 28° C., 29° C., 30° C., 31° C. or 32° C.), and the reaction time is 3-5 h (for example, 3 h, 3.2 h, 3.4 h, 3.6 h, 3.8 h, 4.0 h, 4.2 h, 4.4 h, 4.6 h, 4.8 h or 5 h, etc.);

[0038] In the second stage, the temperature of the reaction system is 35-42° C. (for example, 35° C., 36° C., 37° C., 38° C., 39° C., 40° C., 41° C. or 42° C.), and the reaction time is 1-3 h (for example, 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h or 3 h, etc.);

[0039] In the third stage, the temperature of the reaction system is 45-52° C. (for example, 45° C., 46° C., 47° C., 48° C., 49° C., 50° C., 51° C. or 52° C.), and the reaction time is 1-3 h (for example, 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h or 3 h, etc.);

[0040] In the fourth stage, the temperature of the reaction system is 55-62° C. (for example, 55° C., 56° C., 57° C., 58° C., 59° C., 60° C., 61° C. or 62° C.), and the reaction time is 1-3 h (for example, 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2 h, 2.2 h, 2.4 h, 2.6 h, 2.8 h or 3 h, etc.);

[0041] In the fifth stage, the temperature of the reaction system is 65-72°C (for example, it can be 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C or 72°C, etc.), and the reaction time is 3-5h (for example, it can be 3h, 3.2h, 3.4h, 3.6h, 3.8h, 4.0h, 4.2h, 4.4h, 4.6h, 4.8h or 5h, etc.).

[0042] In the preparation process of the thermosensitive material provided by the present invention, a gradient temperature increase method is used to carry out the polymerization reaction, which can control the morphology of the obtained thermosensitive material, so that the polymerization reaction proceeds gradually, which is conducive to the formation of a large-pore thermosensitive material, thereby further improving the adsorption performance of the obtained thermosensitive material.

[0043] Preferably, if the preparation raw material includes an imprinted ion source, after the reaction is completed, it is necessary to rinse with cold water at least three times and then filter to obtain the thermosensitive material.

[0044] In the present invention, when the raw material for preparing the thermosensitive material contains an imprinted ion source, the thermosensitive material can be prepared using the ion imprinting technology. After the polymerization reaction technology, the imprinted ions can be desorbed by cold water washing, avoiding the dependence on inorganic acids in the desorption process when preparing the adsorbent material using the ion imprinting technology. It is not only simple to operate, but also green and safe. Further, the rare earth ions are desorbed from the thermosensitive material by cold water washing, which can be beneficial to the recycling of the thermosensitive material, and the purpose of separating and recovering rare earth ions economically and efficiently is achieved. The number of cold water washings in the present invention is preferably 3-5 times.

[0045] Preferably, the cold water includes any one of distilled water, ultrapure water or deionized water, or a combination of at least two of them.

[0046] Preferably, the temperature of the cold water is 10°C-30°C, for example, it can be 10°C, 15°C, 16°C, 17°C, 18°C, 19°C, 20°C, 22°C, 25°C, 28°C or 30°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 15-20°C.

[0047] The thermosensitive material provided by the present invention is a hydrogel. When rare earth ions are desorbed by cold water, the temperature of the cold water is controlled at 10°C-30°C, which is lower than the volume phase transition temperature of the obtained thermosensitive material, so that the hydrogel is in a fully swollen state, and the deformed imprinted cavity is enlarged, so that the template ions are released, thereby significantly improving the adsorption of the thermosensitive material. Further, when the temperature of the cold water is lower than 15°C, because desorption is an endothermic reaction, higher temperatures are conducive to desorption, so that the adsorption amount of rare earth ions is reduced. When the temperature of the cold water is higher than 20°C, the material shrinks at a higher temperature, resulting in a decrease in pore size, and the adsorbed ions cannot be released, so that the adsorption amount of rare earth ions is reduced. Therefore, when the temperature of the cold water is 15°C-20°C, the obtained thermosensitive material has a better adsorption effect.

[0048] Illustratively, in the method for preparing the thermosensitive material provided by the present invention, the mass concentration of each preparation raw material in the solvent system is as follows:

[0049] Biomass matrix 1-15g·L -1 , Thermosensitive monomer 7-40g·L -1 、Initiator 30-50g·L -1 , cross-linking agent 1-3g·L -1 、Imprinted ions 5-20mg·L -1 .

[0050] In a third aspect, the present invention provides a rare earth ion adsorption material, wherein the rare earth ion adsorption material comprises the thermosensitive material described in the first aspect.

[0051] Compared with the prior art, the present invention has at least the following beneficial effects:

[0052] (1) The thermosensitive material provided by the present invention has a reversible and stable structure, and has excellent adsorption and selectivity for rare earth ions. At the same time, it can desorb rare earth ions by simply washing with cold water, getting rid of the dependence on acid washing and desorption, and realizing multiple recycling of the adsorbent. After being reused five times, its adsorption rate is maintained at more than 50.0%, providing a good model for the green, efficient and economical separation and recovery of rare earth ions.

[0053] (2) By further optimizing the raw materials for preparing the thermosensitive material of the present invention, the adsorption capacity of rare earth ions can reach 100 mg·g -1In the presence of competitive ions, the adsorption capacity of rare earth ions can still reach 74 mg g -1 At the same time, it has good selectivity for rare earth ions when competing ions exist.

[0054] (3) The preparation method of the thermosensitive material provided by the present invention is simple and can be synthesized by a "one-pot method" polymerization reaction. The entire preparation process is simple to operate, the raw materials are widely available, and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 is the FT-IR spectrum of the thermosensitive material obtained in Example 1;

[0056] Figure 2 The thermosensitive material CITH-La obtained in Example 1 and its adsorbed La 3+ The scanning electron microscope images of the material CITH-La-a obtained after the experiment, the thermosensitive material CITH-Y obtained in Example 3, and the thermosensitive material CNITH obtained in Example 18;

[0057] Figure 3 is a graph showing the variation of the adsorption amount of the thermosensitive material CITH-La obtained in Example 1 and the thermosensitive material CITH-Y obtained in Example 3 with the initial concentration;

[0058] Figure 4 The three heating-cooling cycle DSC graphs of the thermosensitive materials obtained in Example 1 and Example 3 and the volume phase transition temperature statistics graphs of the three tests;

[0059] Figure 5 It is a five-cycle adsorption performance test diagram of the thermosensitive material obtained in Example 1 and Example 3. DETAILED DESCRIPTION

[0060] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0061] The information of some raw materials involved in the specific implementation method is as follows:

[0062] 1000mg·L -1 La 3+ Solution, Nd 3+ Solution, Y 3+ Solutions were all rare earth standards purchased from National Standard (Beijing) Inspection and Certification Co., Ltd.;

[0063] The hydrated nitric acid compounds used to prepare the rare earth adsorption solution were all purchased from Maclean, and other raw materials were commercially available unless otherwise specified.

[0064] Example 1

[0065] This embodiment provides a thermosensitive material, and the preparation method of the thermosensitive material comprises the following steps:

[0066] (1) 1.00 g carboxymethyl chitosan (CMCh), 0.15 g N,N-methylenebisacrylamide (MBA), 4.25 g ammonium persulfate (APS) and 2.11 g N-isopropylacrylamide (NIPAM) (molar ratio n CMCh :n NIPAM =1:10) was added to a three-necked flask, followed by 99 mL of ultrapure water and 1 mL of La 3+ Solution (1000mg·L -1 ).

[0067] (2) The three-necked flask was placed in a constant temperature magnetic stirring oil bath for reaction. The reaction process adopted a gradient heating method. First, the reaction was carried out at 30°C for 3 hours, and then the temperature was gradually increased to 40°C, 50°C and 60°C for 1 hour each. Finally, the reaction system was reacted at 70°C for 3 hours.

[0068] (3) After the polymerization, the obtained hydrogel was filtered and rinsed three times with ultrapure water at 15°C to completely remove the imprinted La 3+ The excess water was then removed by suction filtration to obtain the thermosensitive material CITH-La.

[0069] Example 2

[0070] This embodiment provides a thermosensitive material, and the preparation method of the thermosensitive material comprises the following steps:

[0071] (1) 0.10 g of carboxymethyl cellulose (McLean C804618), 0.10 g of acrylamide, 3.00 g of potassium persulfate and 0.70 g of N-isopropylmethacrylamide were added to a three-necked flask, followed by 99.5 mL of ultrapure water and 0.5 mL of La 3+ Solution (1000mg·L -1 ).

[0072] (2) The three-necked flask was placed in a constant temperature magnetic stirring oil bath for reaction. The reaction process adopted a gradient heating method. First, the reaction was carried out at 25°C for 5 hours, and then the temperature was gradually increased to 35°C, 45°C and 55°C for 3 hours each. Finally, the reaction system was reacted at 65°C for 5 hours.

[0073] (3) After the polymerization, the obtained hydrogel was filtered and rinsed four times with ultrapure water at 20°C to completely remove the imprinted La 3+ The excess water was then removed by suction filtration to obtain the thermosensitive material CITH-La.

[0074] Example 3

[0075] This embodiment provides a thermosensitive material, and the preparation method of the thermosensitive material comprises the following steps:

[0076] (1) 1.50 g carboxymethyl chitosan (CMCh), 0.30 g N,N-methylenebisacrylamide (MBA), 5.00 g ammonium persulfate (APS) and 4.00 g NIPAM were added to a three-necked flask, followed by 98 mL ultrapure water and 2 mL La 3+ Solution (1000mg·L -1 ).

[0077] (2) The three-necked flask was placed in a constant temperature magnetic stirring oil bath for reaction. The reaction process adopted a gradient heating method. First, the reaction was carried out at 32°C for 4 hours, and then the temperature was gradually increased to 42°C, 52°C and 62°C for 2 hours each. Finally, the reaction system was reacted at 72°C for 4 hours.

[0078] (3) After the polymerization, the obtained hydrogel was filtered and rinsed five times with ultrapure water at 20°C to completely remove the imprinted La 3+ The excess water was then removed by suction filtration to obtain the thermosensitive material CITH-La.

[0079] Example 4

[0080] This embodiment provides a thermosensitive material, which is different from the embodiment 1 in that La 3+ Solution (1000mg·L -1 ) is replaced by Nd 3+ Solution (1000mg·L -1 ), other raw materials, addition amounts and preparation methods are the same as those in Example 1, to obtain the thermosensitive material CITH-Nd.

[0081] Example 5

[0082] This embodiment provides a thermosensitive material, which is different from the embodiment 1 only in that La 3+ Solution (1000mg·L -1 ) is replaced by Y 3+ Solution (1000mg·L -1 ), other raw materials, addition amounts and preparation methods are the same as those in Example 1, to obtain the thermosensitive material CITH-Y.

[0083] Example 6

[0084] This embodiment provides a thermosensitive material, which is different from the embodiment 1 only in that the amount of NIPAM added is adjusted from 2.11 g to 0.70 g, so that the molar ratio n CMCh :n NIPAM The ratio was adjusted from 1:10 to 1:3.4, and the other raw materials, addition amounts and preparation methods were the same as those in Example 1 to obtain the thermosensitive material CITH-La.

[0085] Example 7

[0086] This embodiment provides a thermosensitive material, which is different from the embodiment 1 only in that the amount of NIPAM added is adjusted from 2.11 g to 1.41 g, so that the molar ratio n CMCh :n NIPAM The ratio was adjusted from 1:10 to 1:6.8, and the other raw materials, addition amounts and preparation methods were the same as those in Example 1 to obtain the thermosensitive material CITH-La.

[0087] Example 8

[0088] This embodiment provides a thermosensitive material, which is different from the embodiment 1 only in that the amount of NIPAM added is adjusted from 2.11 g to 2.81 g, so that the molar ratio n CMCh :n NIPAM The ratio was adjusted from 1:10 to 1:13.5, and the other raw materials, addition amounts and preparation methods were the same as those in Example 1 to obtain the thermosensitive material CITH-La.

[0089] Example 9

[0090] This embodiment provides a thermosensitive material, which is different from the embodiment 1 only in that the amount of NIPAM added is adjusted from 2.11 g to 3.52 g, so that the molar ratio n CMCh :n NIPAM The ratio was adjusted from 1:10 to 1:17, and other raw materials, addition amounts and preparation methods were the same as those in Example 1 to obtain the thermosensitive material CITH-La.

[0091] Example 10

[0092] This embodiment provides a thermosensitive material, which is different from the embodiment 1 only in that the amount of NIPAM added is adjusted from 2.11 g to 1.25 g, so that the molar ratio n CMCh :n NIPAM The ratio was adjusted from 1:10 to 1:6, and the other raw materials, addition amounts and preparation methods were the same as those in Example 1 to obtain the thermosensitive material CITH-La.

[0093] Embodiment 11

[0094] This embodiment provides a thermosensitive material, which is different from the embodiment 1 only in that the amount of NIPAM added is adjusted from 2.11 g to 2.91 g, so that the molar ratio n CMCh :n NIPAM The ratio was adjusted from 1:10 to 1:14, and other raw materials, addition amounts and preparation methods were the same as those in Example 1 to obtain the thermosensitive material CITH-La.

[0095] Example 12

[0096] This embodiment provides a thermosensitive material, which differs from Embodiment 1 only in that in the preparation step (2) of the thermosensitive material, the gradient heating method is replaced by reacting the reaction system at 70° C. for 9 hours, and other raw materials, addition amounts and preparation methods are the same as those in Embodiment 1, to obtain the thermosensitive material CITH-La.

[0097] Embodiment 13

[0098] This embodiment provides a thermosensitive material, which differs from Embodiment 1 only in that in the preparation step (3) of the thermosensitive material, ultrapure water at 15° C. is replaced with ultrapure water at 10° C., and other raw materials, addition amounts and preparation methods are the same as those in Embodiment 1, to obtain the thermosensitive material CITH-La.

[0099] Embodiment 14

[0100] This embodiment provides a thermosensitive material, which differs from Embodiment 1 only in that in the preparation step (3) of the thermosensitive material, ultrapure water at 15° C. is replaced with ultrapure water at 20° C., and other raw materials, addition amounts and preparation methods are the same as those in Embodiment 1, to obtain the thermosensitive material CITH-La.

[0101] Embodiment 15

[0102] This embodiment provides a thermosensitive material, which differs from Embodiment 1 only in that in the preparation step (3) of the thermosensitive material, ultrapure water at 15° C. is replaced with ultrapure water at 30° C., and other raw materials, addition amounts and preparation methods are the same as those in Embodiment 1, to obtain the thermosensitive material CITH-La.

[0103] Example 16

[0104] This embodiment provides a thermosensitive material, which differs from Embodiment 1 only in that in the preparation step (3) of the thermosensitive material, ultrapure water at 15° C. is replaced with ultrapure water at 25° C., and other raw materials, addition amounts and preparation methods are the same as those in Embodiment 1, to obtain the thermosensitive material CITH-La.

[0105] Embodiment 17

[0106] This embodiment provides a thermosensitive material, which differs from Embodiment 1 only in that CMCh is replaced with chitosan of equal mass, and other raw materials, addition amounts and preparation methods are the same as those in Embodiment 1, to obtain the thermosensitive material CITH-La.

[0107] Embodiment 18

[0108] This embodiment provides a thermosensitive material, and the preparation method of the thermosensitive material comprises the following steps:

[0109] (1) 1.00 g carboxymethyl chitosan (CMCh), 0.15 g N,N-methylenebisacrylamide (MBA), 4.25 g ammonium persulfate (APS) and 2.11 g N-isopropylacrylamide (NIPAM) (molar ratio n CMCh :n NIPAM =1:10) was added into a three-necked flask, followed by 100 mL of ultrapure water.

[0110] (2) The three-necked flask was placed in a constant temperature magnetic stirring oil bath for reaction. The reaction process adopted a gradient heating method. First, the reaction was carried out at 30°C for 3 hours, and then the temperature was gradually increased to 40°C, 50°C and 60°C for 1 hour each. Finally, the reaction system was reacted at 70°C for 3 hours.

[0111] (3) After the polymerization is completed, the obtained hydrogel is filtered to obtain the thermosensitive material CNITH.

[0112] Comparative Example 1

[0113] This comparative example provides an adsorption material, which differs from Example 1 only in that NIPAM is not added, the amount of CMCh added is adjusted from 1.00 g to 3.11 g, and other raw materials, addition amounts and preparation methods are the same as those in Example 1, to obtain the adsorption material CITH-La.

[0114] Comparative Example 2

[0115] This comparative example provides an adsorption material, which differs from Example 1 only in that CMCh is not added, the amount of NIPAM added is adjusted from 2.11 g to 3.11 g, and other raw materials, addition amounts and preparation methods are the same as those in Example 1, to obtain the adsorption material CITH-La.

[0116] The above embodiments and comparative examples were subjected to performance tests, and the test methods and results are as follows:

[0117] (1) The thermosensitive materials described in Examples 1-18 and the adsorption materials described in Comparative Examples 1 and 2 were used as adsorbents to test the adsorption performance:

[0118] A. Single Element System

[0119] The hydrated nitrate of rare earth ions was prepared to a concentration of 1500 mg·L -1 A single element system stock solution is prepared, and the pH of the single element system stock solution is adjusted to 5.0 using acetic acid or ammonia water. 10 mL of the single element system stock solution with a pH of 5.0 is added with 10 mg of the thermosensitive material described in the embodiment or the adsorption material described in the comparative example, and adsorbed at 50° C. for 12 hours. After the adsorption is completed, the adsorbent is filtered, and then the remaining solution is diluted. The residual concentration of rare earth ions after adsorption is measured by ICP-OES, and the adsorption amount of rare earth ions by the sample is calculated according to formula (1):

[0120]

[0121] In formula (1), Q e is the adsorption amount, M is the mass of the adsorbent, V is the volume of the solution, C0 is the initial concentration of the ion, C e is the residual concentration of the ion after adsorption.

[0122] B. Dual element system - selective adsorption

[0123] Preparation of rare earth ions and competing ions (Na + , K + Mg 2+ , Ca 2+ , Cu 2+ 、Al 3+ and Fe 3+ ) was used to prepare a dual-element system stock solution, and the pH of the stock solution was adjusted using acetic acid so that the initial concentrations of the rare earth ions and the competitive ions in the dual-element system stock solution were both 1500 mg·L -1 , the solution pH is 5.0. In addition, due to Fe 3+ It is relatively stable in a strong acidic system and is prone to precipitation when the pH is greater than 4.0. 3+ , the pH of the dual-element system stock solution is 4.0. Take 20 mL of the dual-element system stock solution after adjusting the pH, add 20 mg of the thermosensitive material described in the embodiment or the adsorption material described in the comparative example, and adsorb at 50°C for 12 hours. After the adsorption is completed, filter the adsorbent, and then dilute the remaining solution. Measure the residual concentration of rare earth ions after adsorption and the residual concentration of competitive ions by ICP-OES, and calculate the corresponding adsorption amount and adsorption selectivity according to formulas (1)-(3):

[0124]

[0125] The adsorption selectivity of the adsorbent material can be expressed as the distribution coefficient K d (mL·g -1) and separation factor α; K in formula (3) d1 and K d2 are the distribution coefficients of rare earth ions and competing ions, respectively.

[0126] In the adsorption performance test, when the adsorbent is the thermosensitive material CITH-La, CNITH or adsorbent material CITH-La, the hydrated nitrate of the rare earth ion is lanthanum nitrate hexahydrate (La(NO3)3·6H2O); when the adsorbent is the thermosensitive material CITH-Nd, the hydrated nitrate of the rare earth ion is neodymium nitrate hexahydrate (Nd(NO3)3·6H2O); when the adsorbent is the thermosensitive material CITH-Y, the hydrated nitrate of the rare earth ion is yttrium nitrate hexahydrate (Y(NO3)3·6H2O).

[0127] At the same time, in the specific adsorption performance test, 1mL of rare earth ion solution before adsorption was diluted 50 times with deionized water, and 1mL of the remaining rare earth ion solution after adsorption was diluted 50 times with deionized water, and the corresponding ion concentrations were tested by ICP-OES. The single element system is the case where there is no competing ion, and the adsorbent adsorbs the target ion; the dual element system is the case where the target ion and a competing ion coexist, and the adsorbent adsorbs the ion.

[0128] The test results are shown in Table 1:

[0129] Table 1

[0130]

[0131]

[0132] From the test results in Table 1, we can see that:

[0133] It can be seen from Examples 1 to 5 that the thermosensitive material provided by the present invention has good adsorption and selectivity for rare earth ions. Furthermore, by optimizing the raw materials for preparing the thermosensitive material, the obtained thermosensitive material can be made to be highly selective for La 3+ The adsorption capacity can reach 100 mg g -1 Above, and in the presence of competing ions, for La 3+ The adsorption capacity can still reach 83.87 mg·g -1 .

[0134] By comparing Example 1 with Examples 6-11, it can be seen that as the NIPAM content increases, the adsorption amount of CITH-La shows a trend of first increasing and then decreasing. This is because the amount of thermosensitive monomer increases, the imprinting sites increase, and then the adsorption amount increases. When the thermosensitive monomer is excessive, the thermosensitivity of the material is destroyed, thereby affecting the adsorption amount.

[0135] By comparing Example 1 with Example 12, it can be seen that when the thermosensitive material obtained in Example 12 adopts a fixed temperature reaction instead of a gradient temperature increase during the preparation process, the adsorption performance of the obtained thermosensitive material is significantly reduced, and its selectivity is also poor, indicating that the specific preparation method selected in the present invention can significantly improve the adsorption and selectivity of the obtained thermosensitive material for specific rare earth ions.

[0136] By comparing Example 1 with Examples 13-16, it can be seen that if the thermosensitive material is prepared by ion imprinting technology, the temperature of the cold water in the process of cold water desorption of the template ions has an important influence on the adsorption and selectivity of the obtained thermosensitive material. The cold water washing temperature in Example 13 is 10°C. When it is lower than 15°C, since desorption is an endothermic reaction, a higher temperature is conducive to desorption, so that the adsorption amount of rare earth ions is 90.84 mg·g -1 In Examples 15 and 16, the cold water flushing temperatures are 30°C and 25°C, respectively, both higher than 20°C. Because the material shrinks at a higher temperature, the pore size is reduced, and the adsorbed ions cannot be released, and the corresponding adsorption amount of rare earth ions is not good.

[0137] By comparing Example 1 with Example 17, it can be seen that when chitosan is selected as the biomass matrix in the preparation raw material of Example 17, its adsorption capacity for rare earth ions is 83.48 mg·g -1 , which is significantly lower than the adsorption capacity of rare earth ions by the thermosensitive material obtained in Example 1 (107.40 mg·g -1 , indicating that when the biomass matrix in the present invention is selected as hydroxymethyl chitosan, the abundant amino and carboxyl groups in its structure can increase the imprinting sites (active sites for rare earth ion binding), thereby improving the adsorption and selectivity of the obtained thermosensitive material.

[0138] By comparing Example 1 with Example 18, it can be seen that the thermosensitive material obtained in Example 18 is prepared by non-ionic imprinting technology, and the prepared thermosensitive material has a high sensitivity to La. 3+ The adsorption capacity was only 25.80 mg·g -1 , which is much lower than the La of the thermosensitive material prepared by ion imprinting technology in Example 1 3+ The adsorption capacity was 107.40 mg·g -1 In addition, the thermosensitive material obtained in Example 18 was subjected to Y 3+ The adsorption capacity was 30.2 mg·g -1 , which is significantly lower than the thermal sensitive material obtained in Example 5 for Y 3+ The adsorption capacity was 115.82 mg·g -1, indicating that the adsorption performance of the thermosensitive material prepared by ion imprinting technology for rare earth ions is significantly better than that of the thermosensitive material prepared by non-ionic imprinting technology. Further, by comparing Examples 1-3 with Example 18, it can be seen that the selectivity α of the thermosensitive materials obtained in Examples 1-3 is greater than 20 and can reach up to 125 when there are competing ions, while the selectivity α of Example 18 is not higher than 2 at this time, indicating that due to the presence of specific recognition sites, the selectivity of the thermosensitive material prepared by ion imprinting technology is significantly better than that of the thermosensitive material prepared by non-ionic imprinting technology.

[0139] By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that in Comparative Example 1, no thermosensitive monomer is added during the preparation process, and the adsorption material obtained is 3+ The adsorption capacity was only 15.72 mg·g -1 , while in Comparative Example 2, no biomass matrix was added during the preparation process, and the adsorption material obtained was 3+ The adsorption capacity was only 25.23 mg·g -1 Obviously, the adsorption materials obtained in Comparative Examples 1 and 2 have a 3+ The adsorption capacity of the thermosensitive material obtained in Example 1 is much lower than that of La 3+ The adsorption capacity was 107.40 mg·g -1 , indicating that the specific biomass matrix and the thermosensitive monomer in the present invention can play a synergistic role, thereby greatly increasing the imprinting sites (active sites for rare earth ion binding), thereby significantly improving the adsorption capacity of rare earth ions by the obtained thermosensitive material.

[0140] Figure 1 The Fourier transform infrared (FT-IR) spectrum shown in the figure shows that the corresponding thermosensitive material is prepared in the present invention.

[0141] pass Figure 2 From the scanning electron microscope (SEM) spectra shown, it can be seen that CNITH, CITH-La and CITH-Y all have obvious porous structures, and most of them are macroporous structures. Since CITH-La and CITH-Y are obtained by rinsing the composite hydrogel after polymerization with cold water and then filtering, the temperature is lower than the volume phase transition temperature, the polymer volume swells, and the imprinted ions are released, thus generating more enlarged pores on the polymer material. Compared with CITH-La, CITH-La-a has a smaller pore size, which is because CITH-La adsorbs La at 50.0°C. 3+ , when the temperature is greater than the volume phase transition temperature, the hydrogel shrinks and the imprinted cavity gradually recovers. The morphology and structure of thermosensitive hydrogels can be well explained by thermosensitivity and adsorption mechanisms.

[0142] like Figure 3As shown, 20 mg of the thermosensitive material described in Example 1 or Example 3 was added to 20 mL of a single element stock solution, the pH was 5.0, the temperature was 50.0°C, the adsorption time was 360 min, and when La 3+ and Y 3+ The initial concentration (C0) was between 0.05 and 2.00 mg mL -1 When La changes within the range 3+ / Y 3+ Effect of concentration on the adsorption performance of thermosensitive materials Figure 3 When C0 is less than 1.50 mg·mL -1 When C0 is greater than 1.50 mg·mL -1 When C0 is 1.50 mg·mL -1 When the maximum adsorption amount of the thermosensitive material CITH-La described in Example 1 and the thermosensitive material CITH-Y described in Example 3 was 107.4 mg·g -1 and 114.3 mg·g -1 .

[0143] (2) Thermal sensitivity test

[0144] like Figure 4 As shown, the thermosensitivity of the thermosensitive material CITH-La described in Example 1 and the thermosensitive material CITH-Y described in Example 3 were characterized by DSC measurement. DSC was used to continuously heat-cool-heat in the range of 20.0-80.0°C. This cycle was repeated 3 times. The temperature sensitivity and volume phase transition temperature of the sample were tested by implementing three heating-cooling cycles of the sample. During the three repeated heating and cooling processes, the volume phase transition temperatures of the thermosensitive material CITH-La described in Example 1 were maintained at about 36.3°C and 31.7°C, respectively, and the volume phase transition temperatures of the thermosensitive material CITH-Y described in Example 3 were maintained at about 37.8°C and 34.0°C, respectively. There was no significant difference in the volume phase transition temperatures measured three times, indicating that the thermosensitive materials CITH-La and CITH-Y have reversible thermosensitivity, revealing the presence of a reversible and stable structure in the thermosensitive material provided by the present invention.

[0145] (3) Sustainability testing

[0146] like Figure 5As shown in the figure, the thermosensitive material CITH-La described in Example 1 and the thermosensitive material CITH-Y described in Example 3 were subjected to five "adsorption-desorption" cycles (eluted with cold water at 15°C). As the number of cycles increased, the adsorption amounts of CITH-La and CITH-Y gradually decreased. After five cycles of reuse, La 3+ The adsorption capacity was from 107.4 mg·g -1 Down to 59.3 mg g -1 , Y 3+ The adsorption capacity was from 115.8 mg·g -1 Down to 61.6 mg g -1 , which is mainly due to the incomplete desorption and a certain degree of deformation of the imprinted structure. 3+ and Y 3+ The adsorption amount was maintained above 50.0%, and the recycling experiments showed that both CITH-La and CITH-Y hydrogels were reusable.

[0147] Therefore, the thermosensitive material provided by the present invention not only has good adsorption properties, but can also be greenly regenerated by water washing, providing a good model for efficient and economical separation of different metal ions.

[0148] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A heat-sensitive material, characterized in that: The raw materials for preparing the thermosensitive material include a biomass matrix, a thermosensitive monomer and a cross-linking agent.

2. The heat-sensitive material according to claim 1, characterized in that: The mass ratio of the biomass matrix, the thermosensitive monomer and the cross-linking agent is (1-15):(7-40):(1-3); Preferably, the molar ratio of the biomass matrix to the thermosensitive monomer is 1:(3.4-17), preferably 1:(6.8-13.5).

3. The heat-sensitive material according to claim 1 or 2, characterized in that: The biomass matrix includes any one of cellulose nanofibers, chitin nanofibers, carboxymethyl cellulose, bacterial cellulose, chitosan or carboxymethyl chitosan, or a combination of at least two thereof.

4. The thermosensitive material according to any one of claims 1 to 3, characterized in that: The heat-sensitive monomer includes any one of N-isopropyl acrylamide, N-hydroxymethyl acrylamide, N,N-diethyl acrylamide or N-isopropyl methacrylamide, or a combination of at least two thereof.

5. The thermosensitive material according to any one of claims 1 to 4, characterized in that: The cross-linking agent includes any one of N,N-methylenebisacrylamide, glutaraldehyde or acrylamide, or a combination of at least two thereof.

6. The heat-sensitive material according to any one of claims 1 to 5, characterized in that: The raw materials for preparing the thermosensitive material include an imprinted ion source; Preferably, the imprinted ion source comprises any one of light rare earth ions, medium rare earth ions or heavy rare earth ions, or a combination of at least two thereof; Preferably, the light rare earth ions include any one of lanthanum ions, cerium ions, praseodymium ions or neodymium ions, or a combination of at least two thereof; Preferably, the middle rare earth ions include any one of samarium ions, europium ions, gadolinium ions, terbium ions or dysprosium ions, or a combination of at least two thereof; Preferably, the heavy rare earth ions include any one or a combination of at least two of holmium ions, erbium ions, thulium ions, ytterbium ions, lutetium ions or yttrium ions; Preferably, the mass ratio of the imprinted ions to the biomass matrix is ​​(0.005-0.02):(1-15).

7. The thermosensitive material according to any one of claims 1 to 6, characterized in that: The raw materials for preparing the thermosensitive material also include an initiator and a solvent; Preferably, the initiator comprises any one of ammonium persulfate, azobisisobutyronitrile, benzoyl or potassium persulfate, or a combination of at least two thereof; Preferably, the solvent comprises water; Preferably, the water includes any one of distilled water, ultrapure water or deionized water, or a combination of at least two thereof; Preferably, the mass ratio of the biomass matrix to the initiator is (1-15):(30-50).

8. A method for preparing a thermosensitive material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The raw materials including a biomass matrix, a thermosensitive monomer and a cross-linking agent are mixed and reacted to obtain the thermosensitive material.

9. The method for preparing a thermosensitive material according to claim 8, characterized in that: The mixing is carried out under stirring; Preferably, the stirring is performed in an oil bath; Preferably, the reaction is a gradient temperature increase reaction; Preferably, the gradient temperature rising reaction comprises the following stages: In the first stage, the temperature of the reaction system is 25-32°C and the reaction time is 3-5h; In the second stage, the temperature of the reaction system is 35-42°C and the reaction time is 1-3h; In the third stage, the temperature of the reaction system is 45-52°C and the reaction time is 1-3h; In the fourth stage, the temperature of the reaction system is 55-62°C and the reaction time is 1-3h; In the fifth stage, the temperature of the reaction system is 65-72°C and the reaction time is 3-5h; Preferably, if the preparation raw material includes an imprinted ion source, after the reaction is completed, it is necessary to rinse with cold water at least three times and then filter to obtain the thermosensitive material; Preferably, the cold water comprises any one of distilled water, ultrapure water or deionized water, or a combination of at least two thereof; Preferably, the temperature of the cold water is 10°C-30°C, preferably 15-20°C.

10. A rare earth ion adsorption material, characterized in that: The rare earth ion adsorption material comprises the thermosensitive material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of light rare earth ion imprinted adsorbent for treating rare earth wastewater

    CN103521197A

  • Functional polymer and preparation method thereof, and method for preparing ion imprinted polymer by using functional polymer

    CN115141305A

  • Preparation method of polysaccharide-based thermosensitive metal ion imprinted carbon quantum dot material

    CN108722366A

  • Temperature-sensitive ion-imprinted adsorption material based on polysaccharide, preparation method and application of adsorption material

    CN109967050A

  • Copolymer, rare-earth metal adsorbent, production method thereof, water treatment apparatus and water treatment method

    JP2015172163A